Prevalence and risk factors of atherothrombotic events among 1054 hemophilia patients: A population-based analysis. Issue 3 (March 2015) - Wang, Jiaan-Der; Chan, Wei-Cheng; Fu, Yun-Ching; Tong, Kwok-Man; Chang, Shin-Tsu; Hwang, Wen-Li; Lin, Ching-Heng; Tsan, Yu-Tse
Abstract: Introduction: Reports on the prevalence and risk factors of atherothrombotic events (AEs) are conflicting in persons with hemophilia (PWH). Methods: This study evaluated the prevalence and risk factors of AEs among 1054 male hemophilia patients, using data collected from Taiwan's National Health Insurance Research Database between 1997 and 2010, by comparing variable to those of an unaffected 10540 age- and gender-matched general population. Results: The proportions of all AEs among PWH, including 26 ischemic stroke, 29 coronary artery disease and 5 peripheral arterial disease were comparable to those in the general population. The mean age at diagnosis of AE among PWH was younger than that in the general population: 49.0 (95% CI, 43.6-54.5) and 55.8 years (95% CI, 54.5-57.0), P = 0.019, respectively. PWH with Chronic Obstructive Pulmonary Disease (COPD), hypertension, and hyperlipidemia were associated with greater risk for the occurrence of AEs, with hazard ratios (95% CI) of 3.42 (1.25-9.38), 4.15 (2.11-8.17), and 2.84 (1.39-5.79), respectively. PWH who needed replacement therapy had a lower risk of AEs than those who did not need, with a hazard ratio (95% CI) of 0.41 (0.21-0.81). Conclusions: The study indicated the prevalence of AEs among PWH was comparable to that of the general population. AEs appeared at an earlier age among PWH. COPD, hypertension, and hyperlipidemia were risk factors for AEs. PWH who needed replacement therapy may have a lower risk of AEs. Highlights: The prevalence of AEs among PWH was comparable to that of the general population. AEs appeared at an earlier age among PWH. COPD, hypertension, and hyperlipidemia were risk factors for AE among PWH. PWH who needed replacement therapy may have a lower risk of AE.